Disordered interfaces enable high temperature thermal stability and strength in a nanocrystalline aluminum alloy. (15th August 2021) - Balbus, Glenn H.; Kappacher, Johann; Sprouster, David J.; Wang, Fulin; Shin, Jungho; Eggeler, Yolita M.; Rupert, Timothy J.; Trelewicz, Jason R.; Kiener, Daniel; Maier-Kiener, Verena; Gianola, Daniel S.
Graphical abstract: Abstract: Lightweighting of structural materials has proven indispensable in the energy economy, predicated on alloy design with high strength-to-weight ratios. Modern aluminum alloys have made great strides in ambient temperature performance and are amenable to advanced manufacturing routes such as additive manufacturing, but lack elevated temperature robustness where gains in efficiency can be obtained. Here, we demonstrate the intentional design of disorder at interfaces, a notion generally associated with thermal runaway in traditional materials, in a segregation-engineered ternary nanocrystalline Al–Ni–Ce alloy that exhibits exceptional thermal stability and elevated temperature strength. In-situ transmission electron microscopy in concert with ultrafast calorimetry and X-ray total scattering point to synergistic co-segregation of Ce and Ni driving the evolution of amorphous intergranular films separating sub-10 nm Al-rich grains, which gives rise to emergent thermal stability. We ascribe this intriguing behavior to near-equilibrium interface conditions followed by kinetically sluggish intermetallic precipitation in the confined disordered region. The resulting outstanding mechanical performance at high homologous temperatures lends credence to the efficacy of promoting disorder in alloy design and discovery.